Advances in the study of exosomes in cardiovascular diseases - Zhaobo Zhang; Yuanming Zou; Chunyu Song; Kexin Cao; Kexin Cai; Shuxian Chen; Yanjiao Wu; Danxi Geng; Guozhe Sun; Naijin Zhang; Xingang Zhang; Yixiao Zhang; et al. (Journal of Advanced Research)
Background: Cardiovascular disease (CVD) has been the leading cause of death worldwide for many years. In recent years, exosomes have gained extensive attention in the cardiovascular system due to their excellent biocompatibility. Studies have extensively researched miRNAs in exosomes and found that they play critical roles in various physiological and pathological processes in the cardiovascular system. These processes include promoting or inhibiting inflammatory responses, promoting angiogenesis, participating in cell proliferation and migration, and promoting pathological progression such as fibrosis. Aim of review: This systematic review examines the role of exosomes in various cardiovascular diseases such as atherosclerosis, myocardial infarction, ischemia–reperfusion injury, heart failure and cardiomyopathy. It also presents the latest treatment and prevention methods utilizing exosomes. The study aims to provide new insights and approaches for preventing and treating cardiovascular diseases by exploring the relationship between exosomes and these conditions. Furthermore, the review emphasizes the potential clinical use of exosomes as biomarkers for diagnosing cardiovascular diseases. Key scientific concepts of review: Exosomes are nanoscale vesicles surrounded by lipid bilayers that are secreted by most cells in the body. They are heterogeneous, varying in size and composition, with a diameter typically ranging from 40 to 160 nm. Exosomes serve as a means of information communication between cells, carrying various biologically active substances, including lipids, proteins, and small RNAs such as miRNAs and lncRNAs. As a result, they participate in both physiological and pathological processes within the body.